Motives for Playing Basketball among Female Players of Premium Clubs in Palestine - Eyad yousef; Abdulsalam Al Zaab; Hashem Kilani (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the motives for playing basketball among female players of premium clubs in Palestine, and to determine the relationship of the variables of place of residence, educational qualification and experience in playing with those motives. The researchers used a descriptive survey method for its relevance to the nature of the study on a sample of (72) female players participating in the Basketball Premier League in Palestine for the 2019/2020 sports season, distributed among seven clubs. The researcher applied to the sample a questionnaire which included (37) items divided into five areas: physical fitness motives, recreation motives, social relations motives, travel motives, and psychological motives. The results of the study indicated that the players' motivations to play basketball were high and positive in all of the fields of study. The study recommends the need to pay attention to and strengthen the motives of basketball players in Palestine and encourage women to engage in various sports activities, and work to increase external participation and raise health awareness.